Confronting the zombies Policies for productivity revival - Andrews, Dan (OECD Publishing, 2017)
Policies that spur more efficient corporate restructuring can revive productivity growth by targeting three inter-related sources of labour productivity weakness: the survival of "zombie" firms (low productivity firms that would typically exit in a competitive market), capital misallocation and stalling technological diffusion. New OECD policy indicators show that there is much scope to improve the design of insolvency regimes in order to reduce the barriers to restructuring of weak firms and the personal costs associated with entrepreneurial failure. Insolvency regime reform can not only address the aforementioned sources of productivity weakness but also enhance the productivity impacts of reducing entry barriers in product markets. As the zombie firm problem may partly stem from bank forbearance, complementary reforms to insolvency regimes are essential to ensure that a more aggressive policy to resolve non-performing loans is effective. Distortions in the banking sector highlight the importance of market-based financing instruments for productivity growth with the inherent debt bias in corporate tax systems emerging as a key barrier to technological diffusion. Finally, well-designed job search and retraining policies are effective at returning workers displaced by firm exit to work, particularly in environments where barriers to firm entry are low
Keywords: Economics